Knowledge and Attitudes Related to Behavior of Pregnant Women in Prevention of Covid-19: Pengetahuan dan Sikap Berhubungan dengan Perilaku Ibu Hamil dalam Pencegahan Covid-19 - Artika Dewie; Anna Veronica Pont; Hastuti Usman; Niluh Nita Silfia; Hasnawati Hasnawati; Sri Yanti Kusika (Napande: Jurnal Bidan, 2023)
Background The Central Sulawesi Provincial Health Office noted that until April 7 2021 the number of Covid-19 patients was 11,424. Palu City occupies the maximum number of patients with 3,042 people. One of the groups at risk of exposure to Covid-19 is pregnant women. During the pandemic, pregnant women felt more comfortable doing examinations at the Independent Midwife Practice Place (TPMB) for fear of contracting Covid-19. Purpose This research is to find out the relationship between knowledge and attitudes in pregnant women's behavior toward the prevention of Covid-19 at the Mandiri Midwife Amanah Practice. Methods This quantitative research uses a cross-sectional design using 53 samples of pregnant women who visited TPMB Amanah from June to July 2021. Samples were taken accidentally using a questionnaire instrument. Univariate (frequency distribution) and bivariate data analysis using the kai square test reported in tabular and. Results The research found that most of the respondents had good knowledge, namely 22 respondents (41.5%), had a positive attitude 35 respondents (66%), and behaved not doing 3M totaling 30 respondents (56.6%) with a p-value ≤ 0, 05, which is 0.000. Conclusion There is a relationship between knowledge and attitudes regarding the behavior of pregnant women in preventing Covid-19. It is recommended to actively seek reliable information regarding the prevention of transmission of Covid-19 and get used to carrying out the stages of preventing